Knowledge of coronavirus 2019 and stress with oral health-care personnel of the Faculty of dentistry in Sarajevo: A cross-sectional study (Journal of Health Sciences, 2021)
Introduction: Dentists and generally dental personnel work under the risk of being infected by patients suffering from coronavirus 2019 (COVID-19), who are unaware that they are infected. The reason lies in the fact that during dental procedures, aerosol is formed with droplets that may contain the virus. Thus, it is extremely important that dental personnel comply with adequate protective measures and equipment during clinical work. The aim of this investigation was to evaluate the knowledge of COVID-19 and to determine the amount of stress with dental personnel of the Faculty of Dentistry in Sarajevo, Bosnia and Herzegovina.Methods: Health-care personnel of the Faculty of Dentistry with Clinics of the University in Sarajevo has been included in the research: teaching staff, clinical doctors, dental nurses, and dental technicians. The research was conducted in April 2020. It was conducted by an anonymous survey that participant’s filled-in. Out of 157 distributed questionnaires in paper form, 134 participants responded. The questionnaire was divided into three parts: (1) personal data; (2) knowledge of infection COVID-19 (diagnostic methods, transmission pathways, and prevention measures); and (3) the amount of stress (feelings and thoughts) during epidemic COVID-19 with personnel.Results: The largest number of participants (61.97%) considers that COVID-19 may be transmitted from infected to a healthy person by inhalation of droplets generated through coughing of an infected person and by direct contact with aerosol dispersed from the mouth of the infected patient during dental treatment. The largest number of participants, 80 of them (59.7%) considers that the method of nucleic acid test is used in diagnosing COVID-19. COVID – 19 had a significantly larger influence on females; they showed higher extent of concern for the claim „I hardly fall asleep because of thinking about it,“ „I try not to talk on this topic“ and „In my mind appear pictures in relation to this“ (p < 0.05).Conclusion: Knowledge of COVID-19 and measures of protection of health-care personnel at the Faculty of dentistry with Clinics in Sarajevo is satisfactory. The largest fear of participants was fear of unconsciously transmitting the infection on people close to them and that members of their families become infected with COVID-19.